Formação de acetato de etila a partir do etanol sobre catalisadores de Cu/ZrO2: efeito da carga de cobre nas propriedades físicas e catalíticas - Freitas, Isabel Cristina de (2010)
The ethanol dehydrocoupling in ethyl acetate distinguishes among the reactions of alcohol transformation in products with higher added value. Due to the possibility of obtaining ethanol from biomass in Brazil, the production of ethyl acetate is of great interest, being their production very economical. The ethanol dehydrocoupling in ethyl acetate was studied over Cu/ZrO2 catalysts prepared by impregnation method followed by calcinations in air. The samples with different Cu loadings were characterized by thermal analyze, X-Ray powder diffraction, determination of the specific surface area, temperature-programmed reduction (TPR), decomposition of N2O and X-Ray photoelectron spectroscopy (XPS). TPR results showed the formation of low temperature reduction Cu species (peaks α1, α2 e β) predominant at low loadings of supported Cu in ZrO2, these species are attributed to CuO highly dispersed on support. The increase of Cu loading caused the formation of CuO bulk species with high temperature reduction (peaks γ1 e γ2). XPS results for Cu/ZrO2 reduced catalysts showed that an increase in the Cu loading caused a shift in the Cu 2p3/2 peak to regions of lower biding energy. The spectra of Cu Auger region suggest that a decrease in the Cu loading increases the ratio of Cu+/Cuo species. Catalytic tests for dehydrocoupling reaction of ethanol were carried out at atmospheric pressure and showed an increasing activity per Cu site for ethyl acetate formation with the increase in the dispersion of supported Cu. Furthermore, the by-products formation due the acetaldehyde via aldol condensation occurs on the ZrO2 support surface. Also, it could be seen that catalysts with Cu loading up to 20% showed an increase in the ethyl acetate selectivity with an increase in the Cu loading. This can be attributed to the higher ZrO2 coating by active phase providing the suppression of by-products that are formed via aldol condensation.